African Multi-Site 2-Year Neuropsychological Study of School-Age Children Perinatally Infected, Exposed, and Unexposed to Human Immunodeficiency Virus. (18th December 2019) - Boivin, Michael J; Chernoff, Miriam; Fairlie, Lee; Laughton, Barbara; Zimmer, Bonnie; Joyce, Celeste; Barlow-Mosha, Linda; Bwakura-Dangarembizi, Mutsawashe; Vhembo, Tichaona; Ratswana, Mmule; Kamthunzi, Portia; McCarthy, Katie; et al.
Abstract: Background: Children living with human immunodeficiency virus (HIV) are at neuropsychological risk for cognitive and motor dysfunction. However, few prospective, multi-site studies have evaluated neuropsychological outcomes longitudinally among perinatally infected African children who received early antiretroviral treatment (ART). Methods: We enrolled 611 children aged 5 to 11 years at 6 sites (South Africa [3], Zimbabwe, Malawi, Uganda). Of these, there were 246 children living with HIV (HIV+) who were initiated on ART before 3 years of age in a prior clinical trial comparing nevirapine to lopinavir/ritonavir (International Maternal Pediatric Adolescent Acquired Immunodeficiency Syndrome Clinical Trials [IMPAACT] P1060); 183 age-matched, exposed but uninfected (HEU) children; and 182 unexposed and uninfected (HUU) children. They were compared across 3 assessment time points (Weeks 0, 48, and 96) on cognitive ability (Kaufman Assessment Battery for Children, second edition [KABC-II]), attention/impulsivity (Tests of Variables of Attention [TOVA]), motor proficiency (Bruininks-Oseretsky Test, second edition [BOT-2]), and on the Behavior Rating Inventory of Executive Function (BRIEF). The cohorts were compared using linear mixed models, adjusting for site, child's age and sex, and selected personal/family control variables. Results: The HIV+ cohort performed significantly worse than the HEU and HUU cohorts for all KABC-II, TOVA, and BOT-2 performance outcomes across all 3 time points ( P values < .001). The HUU and HEU cohorts were comparable. For the KABC-II planning/reasoning subtests, the HIV+ children showed less improvement over time than the HUU and HEU groups. The groups did not differ significantly on the BRIEF. Conclusions: Despite initiation of ART in early childhood and good viral suppression at the time of enrollment, the HIV+ group had poorer neuropsychological performance over time, with the gap progressively worsening in planning/reasoning. This can be debilitating for self-management in adolescence. Abstract : Despite antiretroviral treatment initiation in early childhood, the group living with human immunodeficiency virus had poorer longitudinal neuropsychological performance compared to exposed/uninfected and unexposed participants. The gap progressively worsened in the planning/reasoning domain, which was debilitating for adolescent behavioral self-management.